GAMBARAN HASIL PEMERIKSAAN SEROLOGI TREPONEMA PALLIDUM PADA PENDONOR DARAH DENGAN METODE TREPONEMA PALLIDUM RAPID - Indra Elisabet Lalangpuling; Karina Enjelina Adolong; Ketrina Konoralma (Klinikal Sains : Jurnal Analis Kesehatan, 2022)
Blood transfusion service is a health service effort that utilizes blood as a basic material for humanitarian purposes and not for commercial purposes. Blood and blood products can save lives, but they can also be life threatening for the patient because of the possibility of transmitting the infection from the donor. Syphilis or lues is a sexually transmitted infection caused by the Treponema pallidum bacteria that causes skin disorders and can manifest systemic. The purpose of this study was to describe the results of the Treponema Pallidum serological examination on blood donors using the Treponema Pallidum rapid method at UTD Hospital Tk.II R.W. Mongisidi. This research was a descriptive method with a sampling technique determined by accidental sampling. The sample in this study was taken as many as 30 blood donors who met the inclusion criteria. The results showed that there were 22 male respondents (74%), aged around 17-30 years as many as 19 respondents (67%), working as private employees as many as 17 respondents (56%), non-routine blood donors as many as 19 respondents (63). %) and there are as many as 2 respondents (7%) reactive Treponema pallidum The conclusion of this study is that there are 7% of respondents reactive Treponema pallidum.